The Semiotic Visual Analysis Of Non-Verbal Language In Hotel Advertisements - Km Tri Sutrisna Agustia; Putu Chrisma Dewi; Ida Bagus Kurniawan (Denpasar Institute, 2023)
Numerous digital advertisements deviate from the use of nonverbal communication techniques. Instead of conveying information about a particular product, it provides a misleading and incorrect interpretation. Using the theory of visual semiotics, this study seeks to interpret and comprehend the forms of non-verbal language used in digital advertisements to convey information about specific hotel products. The primary objectives of this study are as follows: (1) to describe the structure of advertising components as nonverbal language in digital advertising for hotels marketing in Bali; (2) to describe the relationship between signs and their references as signifiers and signs in digital advertising for hotel marketing; and (3) to describe and provide an overview of recommendations regarding the appropriate role of meaning in digital advertising for hotel marketing. This research design employs qualitative methods for collecting data from research participants in the form of Instagram images. Nonverbal behavior observed in digital advertising, such as facial expressions, gestures, body language, movement, contact, and appearance, is the subject of study. To provide an overview of the applicability of semiotics to the practice of communicating specific information through digital advertising for hotel marketing. This study's findings include the incorporation of semiotic science variables into the design of digital advertisements for hotel marketing. To avoid misunderstandings between advertisers and their intended audiences, it is possible to establish a perfect match between the desired outcome and the intended message. This research also seeks to expand linguistics into emerging disciplines, such as the business world and commercial advertising